LABORATORY TESTING AND MODELING THE INTERFACIAL TRANSITION ZONE OF SLAG-CONCRETE - Han Ay Lie; Nuroji Nuroji (Department of Civil Engineering, Diponegoro University, 2009)
The transition zone at the aggregate surface has a distinctive formation, in terms of its mechanical as well as its physical properties. This layer is recognized as the ITZ (Interfacial Transition Zone) and considered the “weak link”, since micro cracks are commonly initiated in this area. The properties of this ITZ are jet to be investigated. SEM (Scanning Electron Microscope) images only provide qualitative information such as formation, type and relative amount of crystals. Therefore, other means are required to represent a better understanding to the behavior of the ITZ. The mechanical and physical properties of the ITZ are highly influenced by the differentiation in porosity and strength. A mathematical or FEM (Finite Element Model) can be used to bridge this lack of information. This paper deals with the the modeling approach of ITZ as well as the concept of laboratory testing for validation of the model. Keywords: labour group composition, SNI 2002, field labour’s productivity, middle-class housing. ABSTRAK Daerah peralihan antara agregat dan mortar memiliki susunan struktur dan sifat mekanis yang berbeda dengan mortar yang berjauhan dari agregate. Daerah ini dikenal sebagai ITZ (Interfacial Transition Zone) dan diketahui sebagai daerah yang “lemah” karena retak mikro biasanya diawali di ITZ ini. Perilaku mekanis ITZ sangat sulit ditentukan secara tepat, pengamatan menggunakan SEM (Scanning Electron Microscope) hanya dapat memberikan gambaran secara kualitatif, berupa perilaku bentuk, susunan dan jumlah kristal sehingga perlu adanya pendekatan lain yang dapat memberikan nilai kuantitatif terhadap perilaku ITZ. Pengamatan terhadap sifat mekanis dan fisis ITZ terhadap mortar menunjukkan perbedaan kadar pori dan kekuatan. Untuk menggambarkan konfigurasi pori dan kekuatan ITZ dapat digunakan model, baik model matematis atau FEM (Finite Element Model) yang divalidasi dengan hasil pengujian laboratorium. Tulisan ini membahas konsep permodelan ITZ serta metoda validasi di laboratorium. Kata kunci: model, interfacial transition zone, mortar, aggregate, kekakuan